Where National Medicines Policies Have Taken Us With Patient Involvement and Health Technology Assessment in Africa - Sehmi, Kawaldip; Wale, Janet L. (Frontiers in Medical Technology, 2022)
The Covid-19 pandemic has highlighted global knowledge about, but lack of equitable access to, life-changing medicines, and other innovative medical products by populations in African low and middle income countries. The World Health Organization (WHO) and other international non-profit foundations and organizations are constantly striving to address inequity. In the 1970s, WHO initiated a regularly updated essential medicines list, together with the concept of national medicines policies (NMPs) to ensure access and availability, affordability, rational, and effective use of medicines which are considered essential in addressing predominant population health issues and disease burden. We studied the NMPs of Ghana, South Africa, Uganda and Zimbabwe to highlight some of the important issues that these countries experience in the safe and effective use of medical products. Thailand is an example of how health technology assessment (HTA) can provide a country with an internationally supported, clearly defined and transparent process to broaden access to medicines and services. These medical services can add considerable value in accordance with local values and priorities. Involvement of civil society adds democratic legitimacy to such processes. Community health workers and patient advocacy groups are important in raising awareness and knowledge of safety issues and the effective use of quality medicines. They can apply pressure for increased funding to improve access to healthcare. Medicines and services that contribute to supported self-care are of benefit in any setting. Joint efforts across African countries such as with the African Medicines Agency are important in addressing some of the major health issues.